Evolution and domestication of lima bean in Mexico : Evidence from ribosomal DNA - Serrano Serrano, Martha L.; Andueza-Noh, RH; Martínez Castillo, J.; Debouck, Daniel G.; Chacón Sánchez, María I. (Wiley, 2012)
Phaseolus lunatus L., Lima bean, has been domesticated at least twice in the Americas, once in the Andean region and at another time in Mesoamerica; however, the domestication history of this crop in the latter region remains unclear. In this study, a phylogeographic analysis of DNA polymorphisms in the internal transcribed spacer (ITS) region of the ribosomal DNA from a collection of wild and domesticated accessions was applied to establish where and how many times in Mesoamerica Lima bean was domesticated. The results showed evidence for two wild Mesoamerican gene pools with contrasting geographical distributions. While the MI gene pool occurs in central western Mexico, including the Pacific coastal range, the MII gene pool is widespread and occurs toward the Gulf of Mexico, the Yucatan peninsula, and Central and South America. In a cluster analysis, all Mesoamerican landraces clustered together with wild accessions from the MI gene pool (L haplotype) suggesting a unique domestication event in central western Mexico. The most likely domestication region is an area of the states of Nayarit–Jalisco or Guerrero–Oaxaca and not areas such as the Peninsula of Yucatan where the crop is currently widespread and diverse. A strong founder effect due to domestication was quantified and several recently diversified haplotypes were identified. A hypothesis about possible dispersal routes of the crop within Mesoamerica is proposed as well as an apparent late adoption of the crop into the milpa system.